Topochemical Synthesis of 2D Carbon Hybrids through Self‐Boosting Catalytic Carbonization of a Metal–Polymer Framework. Issue 50 (15th November 2018) - Zhang, Qiao; Zhou, Yanping; Xu, Feng; Lin, Huijuan; Yan, Yan; Rui, Kun; Zhang, Chenjun; Wang, Qingqing; Ma, Zhongyuan; Zhang, Yao; Huang, Kama; Zhu, Jixin; et al.
Abstract: Two‐dimensional (2D) carbon hybrids have promise in various areas such as energy storage and catalysis. Simple methods for controllable fabrication of 2D graphitic carbon hybrids in a scalable manner remains challenging. Now, a microwave‐assisted strategy for mass production of 2D carbon hybrids based on self‐boosting catalytic carbonization of a metal–agarose framework is demonstrated. Hybrids including hollow Fe3 C nanoparticles, Ni/Co nanoparticles, and hollow FeOx nanoparticles uniformly embedded in 2D graphitic carbon nanosheets (GCNs) are obtained, demonstrating the generality of the approach. Metal–polymer coordination and microwave‐enabled fast catalytic decomposition of precursors play vital roles in facilitating the formation of the nanosheet structure. The resulting FeOx ‐GCNs hybrid exhibits superior lithium‐storage performance (1118 mAh g −1 at 500 mA g −1 and 818 mAh g −1 at 2000 mA g −1 after 1200 cycles). Abstract : Superdrying : Microwave‐enabled fast evaporation of water and decomposition of nitrate converted a metal–agarose framework into a 2D nanosheet structure. Using this approach, hybrids such as hollow Fe3 C nanoparticles, Ni/Co nanoparticles, and hollow FeOx nanoparticles uniformly embedded in 2D graphitic carbon nanosheets could be obtained after annealing.